ANALYSIS OF FINANCIAL LITERACY, EDUCATION LEVEL ON FINANCIAL TECHNOLOGY GEN Z, MEDIATED BY SELF- EFFICACY - Erna Apriani; Abdul Latif; Indra Permana; Akfika Rizky Sabilla (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
This study aims to analyze the direct role of financial literacy and education level on financial technology, secondly to analyze the direct influence of financial literacy and education level on self-efficacy, thirdly to analyze the direct influence of self-efficacy on financial technology, and fourthly to analyze the indirect influence of financial literacy and education level on financial technology through the mediation of self-efficacy. The sample was 100 Generation Z individuals in Bekasi Regency, selected using purposive sampling. The data analysis method in this study was associative causality through a quantitative approach. The data analysis technique used is SEM-PLS (Structural Equation Modeling-Partial Least Squares) on financial literacy, education level, financial technology, and self-efficacy as a mediating variable. The study results show that financial literacy does not affect financial technology. However, financial literacy has a significant effect on self-efficacy. Education level does not affect financial technology, but education level significantly affects self-efficacy. Self-efficacy mediates educational level and financial technology. The practical implications of this study related to financial literacy and education are that they increase Gen Z's self-efficacy in using financial technology (fintech), which affects their ability to manage finances effectively, avoid financial problems, and access appropriate financial products.